Pattern of Serum Cortisol Levels in Different Thyroid Disorders (Med Phoenix, 2024)
Introduction: Thyroid disorders are now common endocrinological issues with an ample number of cases with the most abundant cases of hypothyroidism. Serum cortisol levels have been found to be deranged in cases of thyroid disorders. The thyroid disorders have impact on adrenals glands that produces cortisol. In hypothyroidism, high cortisol results in increase cortisol half-life and also decrease of metabolic clearance. However, control mechanisms often allow normal cortisol values. This study was carried out with an aim to evaluate the serum cortisol in different thyroid disorders and to correlate the relation of serum cortisol with thyroid hormones.Materials and methods: This hospital based cross sectional descriptive study was carried out in a tertiary care center of Madesh   province, National Medical College Teaching Hospital in a time frame for six month from September 2022 to February 2023. A total of 300 samples were enrolled in the study (100 hyperthyroid, 100 hypothyroid and 100 euthyroid as control) after taking a well informed written consent and prior ethical clearance. The thyroid function test and serum cortisol was estimated and data were put in Microsoft excel 2010 and analyzed using SPSS version 22.Results: This study showed that there was highly significant difference in the highest level of sensory block achieved between the two groups (p < 0.001 ) and motor blockade. Most of patients receiving bupivacaine alone (Group B) had achieved T6 dermatomal sensory level block and Bromage score of 4, while patients receiving fentanyl with bupivacaine (Group F) achieved T8 and also Bromage score of 3 respectively. The mean duration for highest sensory level in group F and group B was 7.76 and 9.66 minutes, respectively. The mean duration for 2 segment regression in group F and group B was 95.28 and 67.24 minutes respectively. Hypotension was significantly high in Group B.Conclusion: The study concluded that serum cortisol level is elevated in cases of hypothyroidism, particularly in frank primary hypothyroidism. However, the mean cortisol levels were found to be normal in other thyroid disorders.